EKSISTENSI JURNALISME DI ERA MEDIA SOSIAL - Dian Muhtadiah Hamna (Fakultas Dakwah dan Komunikasi, 2017)
Social media that appear lately indeed change the panorama of journalism in Indonesia. Especially concerning the process of gathering news, the process of making news, and the process of spreading the news. Future Journalism-the old and the new-should refer to how people use the news and what they need from journalists.